Modeling of methane steam reforming in a microchannel subject to multicomponent diffusion - Kuznetsov, V. V.; Kozlov, S. P. (Journal of engineering thermophysics, 2011)
Catalytic methane steam reforming in a slot microchannel under external heat supply to the mixture reacting on walls is considered based on numerical simulation of a complete system of Navier-Stokes equations. Three ways of heat supply to channel walls are represented, namely, a uniform heat flux, a heat flux linearly decreasing in channel length, and a heat flux following the reaction rate profile of the main reaction. The thermophysical parameters of the mixture depend on its temperature and composition. Two diffusion models are considered, namely, models with equal and different diffusion coefficients for each mixture component. It is shown that consideration of multicomponent diffusion does not practically affect the concentration of the components and the methane reforming at the outlet. For the above-mentioned ways of heat supply, the methane reforming with a heat flux linearly decreasing in channel length is most significant.